2017
DOI: 10.15330/cmp.9.1.28-36
|View full text |Cite
|
Sign up to set email alerts
|

Superextensions of three-element semigroups

Abstract: A family $\mathcal{A}$ of non-empty subsets of a set $X$ is called an upfamily if for each set $A\in\mathcal{A}$ any set $B\supset A$ belongs to $\mathcal{A}$. An upfamily $\mathcal L$ of subsets of $X$ is said to be linked if $A\cap B\ne\emptyset$ for all $A,B\in\mathcal L$. A linked upfamily $\mathcal M$ of subsets of $X$ is maximal linked if $\mathcal M$ coincides with each linked upfamily $\mathcal L$ on $X$ that contains $\mathcal M$. The superextension $\lambda(X)$ consists of all maximal linked upfamili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Proof. In [21,Theorem 3] it was shown that the superextension of a right (left) zero semigroup is a right (left) zero semigroup as well. Each permutation on a right (left) zero semigroup is an automorphism.…”
Section: X|mentioning
confidence: 99%
See 4 more Smart Citations
“…Proof. In [21,Theorem 3] it was shown that the superextension of a right (left) zero semigroup is a right (left) zero semigroup as well. Each permutation on a right (left) zero semigroup is an automorphism.…”
Section: X|mentioning
confidence: 99%
“…Proof. In [21,Theorem 2] it was shown that the superextension of an almost null semigroup is an almost null semigroup as well. Taking into account that z is the zero of the semigroup λ(OA X ) and a is the unique idempotent in λ(OA X ) \ {z}, we conclude that ψ(z) = z and ψ(a) = a for any ψ ∈ Aut (λ(AO X )).…”
Section: The Semigroups λ(Ao X )mentioning
confidence: 99%
See 3 more Smart Citations